ISLAM DI PAPUA BARAT: TRADISI DAN KEBERAGAMAN - Wekke, Ismail Suardi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2013)
It was well known that Papua as large population of non muslim society. In fact, muslim already establish their community on 1512. Therefore, it is a need to explore how the existence of muslim in West Papua province nowdays. This research was applied qualitative approach which is grounded theory. In finding data, observation and in-depth interview were conducted. In addition, the main instrument was researcher itself, and then other instruments are observation sheet and interview guidance. This research shows three things, they are leadership and tradition, religiousity and diversity, and learning spirit. Those kinds of main findings means that muslim in the region not only preserve their tradition but also try to maintain the harmony to other religions. This attitude did not arise spontaneously, there was a long history of co-exist with the others as a family.